APHICIDAL ACTIVITY OF PLANT EXTRACTS AGAINST APHIS FABAE (SCOPOLI, 1763) (HEMIPTERA : APHIDIDAE) (Acta Entomologica Serbica, 2018)
The excessive use of pesticides has created many problems for both human health and the environment. Therefore, the search for alternative methods has become a necessity. This study aims to test the effect of aqueous extracts of three plant species (Pistacia atlantica, Marrubium vulgare and Thymus algeriensis) on the larvae of the black bean aphid (Aphis fabae) found on the faba bean (Vicia faba) under laboratory conditions.With regard to extraction, two methods were adopted for the three plants: maceration and infusion. Each mixture of plant powder and distilled water was filtered and then diluted to obtain three concentrations (5, 15 and 25%). Three replications of 18 aqueous extracts and a control (distilled water) were tested for their insecticidal effect on the aphid mortalities by counting the dead larvae 6, 12 and 24 h after their placement on treated bean leaflets. In addition, phytochemical screening was carried out to detect the presence of saponins and polyphenols in the studied extracts.Through our study, the maceration extract from T. algeriensis at a concentration of 25% was the most effective, with a 70% of larval mortality rate after 24 h. With respect to phytochemical screening, differences in chemical composition were observed between the analyzed extracts (such as the absence of saponins in P. atlantica and its presence in T. algeriensis), which may have a role in the efficacy of the examined treatments.T. algeriensis extracts may be considered among the tools of integrated pest management (IPM) to minimize the use of synthetic pesticides.